If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 = -1 + 8 Reorder the terms: -4 + x = -1 + 8 Combine like terms: -1 + 8 = 7 -4 + x = 7 Solving -4 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + x = 7 + 4 x = 7 + 4 Combine like terms: 7 + 4 = 11 x = 11 Simplifying x = 11
| 2x+4=5-6x | | 16-3x=-4(4x+3) | | 4(x-8)/5=16 | | 2y+(6+y)=12 | | x-8=6x-13 | | B^5=368 | | 2x+3=51-2x | | 2x+18-4x+12=-6 | | -2=2+(.25)v | | 4(3+c)=3(c-5) | | (x-3).6(x+1)=65 | | 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 |